SHORTTERM TRAINING PROGRAM FOR THE PREPARATION PERIOD IN THE ENDURANCE DISCIPLINE OF EQUESTRIAN SPORT - Nedkova-Ivanova, Ruzha; Valev, Yuri (Scientific Publishing House. NSA Press, 2020)
ABSTRACT The competitive pairs of horse and rider in the endurance discipline of equestrian sport in Bulgaria have ranked, in the past several years, among the elite contestants in Europe and the world, which has necessitated deeper studies in the areas of training methods and the ways of achieving high sport results. Therefore, this study is focused on 6 Bulgarian horses (Arabian horse and Shagya, Table 1) that are preparing for European and World championships. They were trained together under the same conditions (climate, time zone, terrain, speed) by riders with the necessary qualifications and experience. Seven training rides were performed, and the pulse was measured at the moment of the highest load, as it is the most indicative of the horse's level of effort. By studying the pulse of horses during a training session, the research aimed to determine the efficacy of the short-term training program in the prep season. The results showed that 2 to 4 minutes after coming to a full stop, regardless of the terrain, speed (in this research between 5.2 km/h and 22.5 km/h) or distance traveled by the horses, their pulse varied between 36 and 99 bpm (beats per minute) and they improved their physical condition and increased their stamina without this leading to trauma or more serious injuries, which is a main priority in the equestrian sport and allows for the successful completion of every race. In the long run, such a training methodology will allow the horses to be trained and ready to race at any time. Monitoring the heart rate and keeping it within the studied limits showed that this was the optimal option for a training regime for the six examined horses. In the situation with the COVID19 pandemic, this is a possible solution for maintaining athletic fitness in endurance horses.